The importance of autonomy of European Union member states with regard to the use of genetically modified organisms on the right to healthcare – an analysis of judgements of the Court of Justice of the European Union - Meško Kuralt, Katja (Lexonomica, 2022)
The European Union Member States (hereinafter: EU MS) have the possibility of restricting or banning the cultivation of GMOs under the Directive 2015/412 but under certain conditions. EU MS must also pay attention to the provisions of the Treaty on the Functioning of the Euro-pean Union or Treaty Establishing the European Community (hereinafter: TFEU), the provi-sions relating to the free movement of goods, which is one of the key objectives of the func-tioning of the European Union. This contribution is based on the data obtained from an analy-sis of Court of Justice of the European Union (hereinafter: CJEU) cases concerning the use of genetically modified organisms (hereinafter: GMO(s)). The analysis highlights the link between environmental risk assessment and the right to healthcare. The purpose of this paper is to make the individual aware of the possibilities they have regarding the use of GMOs.
Keywords: Directive 2001/18; Directive 2015/4120; Directive 2018/350; environmental risk assessment; free movement of goods; high level of protection of human life and health; possibility of restricting or prohibiting the production of GMOs